Understanding the Iranian motivations for possessing nuclear capabilities - Mahboub, Tamer (AUC Knowledge Fountain, 2013)
Research Question: Why would Iran insist on pursuing its nuclear ambiguity policy despite its status as a party to the NPT and international sanctions? The study findings indicate that although there is no conclusive proof that Iran has a weapons program, Iran could be pursuing a strategy of a nuclear ambiguity; the possibility it may have a weapons program acts as a deterrent against potential existential threats to its national security. These findings were based on evidence gathered through interviews with various experts, and conducting a comparison between the conventional weapons possessed by Iran and those possessed by neighboring countries in light of the nature of the existential threats that face Iran. Iran feels that it lives in a hostile environment in the region, and faces collective threats from its adversaries which threaten its national security. Hence, nuclear weapons, or the threat of, could balance nuclear threats that cannot be dealt with through conventional weapons.